Color-Coding Assistance to Improve Students’ Literacy and Numeracy in Biology Learning - Mega Silvianti; Syamsurizal; Lufri; Moralitha Chatri; Suci Fajrina (Jurnal Pendidikan Indonesia, 2026)
Improving students’ literacy and numeracy skills remains a major challenge in biology education, as conventional teaching methods and less engaging instructional media often hinder meaningful learning. This condition can lead to suboptimal achievement of learning objectives. This study aims to examine the effect of the Problem-Based Learning (PBL) model assisted by color coding on students’ literacy and numeracy skills in the ecosystem topic. A quantitative approach with a pre-test–post-test control group design was employed. The sample consisted of two classes at Phase E level, with the experimental group taught using PBL assisted by color coding and the control group taught using Direct Instruction. Data were collected using validated multiple-choice tests designed to measure literacy and numeracy skills. The data were analyzed using normality and homogeneity tests, an independent t-test, and N-Gain calculations. The results indicate a significant improvement in the experimental group, with literacy skills increasing by 19.71% and numeracy skills by 28.51%. These findings suggest that color-coded PBL effectively enhances students’ ability to process information, analyze data, and develop critical and numerical thinking skills.